Analisis penerapan sistem informasi akuntansi dan pengendalian internal terhadap kualitas laporan keuangan pada Koperasi Serba Usaha (KSU) Kencana Makmur Sugihan Tahun 2017 – 2020 - Wijaya, Kusuma; Ihsan Al Faruq, Saiful (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
One of the factors supporting the quality of financial reports is the accounting information system and internal control. This study aims to test the analysis of internal control and the application of accounting information systems to the quality of financial reports at the Kencana Makmur Sugihan 2017-2020 Multipurpose Cooperative (KSU). This research uses quantitative analysis methods. The population in this study were all employees of the KSU Kencana Makmur Sugihan, totaling 60 people, while the sample in this study were employees of accounting, administration (bookkeeper), and internal auditors as many as 40 respondents. The data collection method used questionnaires, the data analysis method used multiple linear regression analysis, and the data processing process used SPSS (Statistical Package for Social Science) version 20. The results showed that the analysis of internal control and the application of accounting information systems simultaneously affected the quality of financial reports. whereas partially the application of accounting information systems and internal controls has a significant effect on the quality of financial reports. Â